Pengembangan Sistem Pengendalian Internal Atas Pengendalian (Studi Kasus PT Sinarmas Multifinance Bandung) - Robby Pangestu; Sugih Sutrisno Putra (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Sales is one of the important aspects for a company to make a profit. Credit sales doesn’t allow company to receive cash as a directly, but can caused account receivables from customer. Lack of receivable control directly will harm the company. Therefore, an internal control system is needed in order to reduce the possibility of bad debt. As with Sinarmas Multifinance Bandung, there are still bad debts by its customers. Therefore it is necessary to do an evaluation to assess how effective and efficient the existing internal control system is. Researcher in this study will conduct an evaluation and analysis also provide recommendations for the internal control system at Sinarmas Multifinance Bandung with descriptive qualitative methode with case study approach and documentation, observation, and interviews conducted in data collection. Internal control system recommendations that will be made by the author will be in the form of Standard Operational Procedure (SOP). Based on the research that the existing of Internal Control System is sufficient. However, there are still some things that must be maximized, so that the authors give recommendations of Internal Control System to maximize existing of Internal Control System.